Associations of linear growth and weight gain in the first 2 years with bone mass at 4 years of age in children in Dhaka, Bangladesh - Maimuna Gias; Huma Qamar; Farzana Fariha; Abdullah Al Mahmud; Prakesh Shah; Steven A Abrams; Daniel E Roth; Karen M O'Callaghan
Abstract Objective: Growth faltering is widespread in many low- and middle-income countries, but its effects on childhood bone mass accrual are unknown. The objective of this study was to estimate associations between length (conditional length-for-age z-scores, cLAZ) and weight (conditional weight-for-age z-scores, cWAZ) gain in 3 age intervals (ages 0-6, 6-12, 12-24 months) with dual-energy x-ray absorptiometry (DEXA)-derived measures of bone mass (total-body-less-head (TBLH) bone mineral content (BMC), areal bone mineral density (aBMD), and bone area) at 4 years of age. Design: Associations between interval-specific growth parameters (cLAZ and cWAZ) and bone outcomes were estimated using linear regression models, adjusted for maternal, child, and household characteristics. Setting: Data collection occurred in Dhaka, Bangladesh. Participants: 599 healthy children enrolled in the BONe and mUScle Health in Kids Study. Results: cLAZ in each age interval was positively associated with TBLH BMC, aBMD, and bone area at 4 years; however, associations attenuated towards null upon adjustment for concurrent height-for-age z-scores (HAZ) at age 4 years and confounders. cWAZ from 0-6 and 6-12 months was not associated with bone mass, but every SD increase in cWAZ between 12-24 months was associated with greater BMC (7.6g; 95%CI:3.2, 12.0) and aBMD (0.008g/cm2; 95%CI:0.003, 0.014) after adjusting for concurrent WAZ, HAZ, and confounders. Conclusions: Associations of linear growth (birth to 2 years) with bone mass at age 4 years were explained by concurrent HAZ. Weight gain in the second year of life may increase bone mass independently of linear growth in settings where growth faltering is common.